Emerging Directions in Embedded and Ubiquitous Computing
DOI: 10.1007/978-3-540-77090-9_63
|View full text |Cite
|
Sign up to set email alerts
|

Security Analysis of the Certificateless Signature Scheme Proposed at SecUbiq 2006

Abstract: Abstract. In this paper, we show that the certificateless signature scheme proposed by Yap, Heng and Goi at SecUbiq 2006 is insecure against a key replacement attack and a malicious-but-passive KGC attack, respectively. The former implies that anyone who replaces a signer's public key can forge valid signatures for that signer without knowledge of the signer's private key. The latter supposes the malicious-but-passive KGC, which generates system parameters based on the information of the target user to imperso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In their scheme, the signing algorithm does not require pairing computation and the verification algorithm only needs two bilinear pairing computations. Unfortunately, Park and Kang found that the scheme of Yap et al is insecure against a key replacement attack. Zhang attack.…”
Section: Introductionmentioning
confidence: 99%
“…In their scheme, the signing algorithm does not require pairing computation and the verification algorithm only needs two bilinear pairing computations. Unfortunately, Park and Kang found that the scheme of Yap et al is insecure against a key replacement attack. Zhang attack.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al also proposed a new CLS scheme. Some relatively more efficient and secure CLS schemes [9,11,14] were proposed to overcome this high computational cost. However, because Hu et al [6] showed that their scheme cannot resist type 1 adversaries, Yum and Lee improved their scheme.…”
Section: Related Workmentioning
confidence: 99%
“…However, these three schemes require three or four pairing operations for signature verification. Some relatively more efficient and secure CLS schemes [9,11,14] were proposed to overcome this high computational cost.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Gorantla and Saxena [5] proposed an efficient CLS scheme, but Cao et al [6] showed that their scheme is insecure against Type I adversary. Since then, many CLS schemes [7][8][9][10][11][12][13][14][15] have been proposed. However, only few of them, for example, [10][11][12], are secure against these two types of adversaries; others are vulnerable to the key replacement attack.…”
Section: Introductionmentioning
confidence: 99%